Professional training in organic food production: a cross-country experience. Issue 3 (6th May 2017) - Guiné, Raquel; Costa, Daniela; Correia, Paula; Costa, Cristina; Correia, Helena; Castro, Moises; Guerra, Luis; Seeds, Catherine; Coll, Collette; Radics, Laszlo; Arslan, Meahmet; Soylu, Soner; et al.
Abstract : Purpose: The purpose of this paper is to characterize the agricultural activities and past experiences in professional training in the context of mobile learning in different countries (Portugal, Spain, Slovakia, Hungary, UK, Italy and Turkey). Design/methodology/approach: For the survey, a questionnaire was prepared in English and Portuguese and then translated into the languages of the participating countries. It was delivered electronically for answering online by adults only. The participation was voluntary and in the end 133 consented valid questionnaires were obtained. For the treatment of the data, SPSS was used and basic descriptive statistics tools were applied, together with tests, namely, crosstabs and χ 2 tests, considering a level of significance of 5 percent. Findings: The results showed that the majority of the participants presently have some agricultural activity and one-third is thinking about starting one in the future. Most of the participants want to produce food organically, with significant differences among the countries studied in this paper. Most of the participants were enrolled in training activities in agriculture, especially those with higher education. This participation showed significant differences between countries as well as according to the dimension of the farms owned by the participants. A significant association was found between being a teacher in forming activities related to agriculture and being a farmer. When compared to distance learning, the training activities in classroom were the most frequent, with significant differences among the countries. Practical implications: This study allowed characterizing the learning activities in the field of organic agriculture and established vision for planning of future training programs, in different countries, with maybe different social, educational and cultural realities. Originality/value: Because the study included the participation of people from several countries all around Europe, the results obtained enrich the scientific area of training in organic farming, in view of distance learning vs classroom learning on a more global basis.